Comparative metagenomic analysis of microbial taxonomic and functional variations in untreated surface and reclaimed waters used in irrigation applications. (1st February 2020) - Chopyk, Jessica; Nasko, Daniel J.; Allard, Sarah; Bui, Anthony; Treangen, Todd; Pop, Mihai; Mongodin, Emmanuel F.; Sapkota, Amy R.
Abstract: The use of irrigation water sourced from reclamation facilities and untreated surface water bodies may be a practical solution to attenuate the burden on diminishing groundwater aquifers. However, comprehensive microbial characterizations of these water sources are generally lacking, especially with regard to variations through time and across multiple water types. To address this knowledge gap we used a shotgun metagenomic approach to characterize the taxonomic and functional variations of microbial communities within two agricultural ponds, two freshwater creeks, two brackish rivers, and three water reclamation facilities located in the Mid-Atlantic, United States. Water samples (n = 24) were collected from all sites between October and November 2016, and filtered onto 0.2 μm membrane filters. Filters were then subjected to total DNA extraction and shotgun sequencing on the Illumina HiSeq platform. From these data, we found that Betaproteobacteria dominated the majority of freshwater sites, while Alphaproteobacteria were abundant at times in the brackish waters. One of these brackish sites was also host to a greater abundance of the bacterial genera Gimesia and Microcystis. Furthermore, predicted microbial features (e.g. antibiotic resistance genes (ARGs) and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) arrays) varied based on specific site and sampling date. ARGs were found across samples, with the diversity and abundance highest in those from a reclamation facility and a wastewater-impacted freshwater creek. Additionally, we identified over 600 CRISPR arrays, containing ∼2600 unique spacers, suggestive of a diverse and often site-specific phage community. Overall, these results provide a better understanding of the complex microbial community in untreated surface and reclaimed waters, while highlighting possible environmental and human health impacts associated with their use in agriculture. Graphical abstract: Image 1 Highlights: Metagenomes from irrigation water sources were analyzed across time and among different sites. Proteobacteria, especially Betaproteobacteria, dominated the majority of sites. Alphaproteobacteria were abundant at specific times in the brackish river samples. Genes associated with pathogenesis were detected at all sites. ARG and CRISPR abundance/diversity varied based on specific site and sampling date.